Neuroscience-Based Learning in Early Childhood Education to Shape Character - Sari Z, Dinda Nopiana; Aryani, Ririn (Green Publisher Indonesia, 2026)
Neuroscience-based learning is an educational approach that emphasizes the integration of how the brain, emotions, and children’s learning experiences interact. This research aims to analyze the role of neuroscience-based learning in early childhood education as an effort to develop character holistically. Through a literature review of various theories and previous research findings, this study highlights how positive stimulation, a safe learning environment, and healthy social interaction contribute to brain development and the formation of children’s character values. The results of the study show that learning aligned with the brain’s working mechanisms can foster empathy, independence, responsibility, and self-control. In addition, this approach encourages teachers to act as facilitators who understand differences in children’s learning styles and create brain-friendly learning environments. Although its implementation in Indonesia still faces challenges, particularly regarding educators’ neuroscience literacy, this approach has the potential to become an essential foundation for early childhood character education in the future. Thus, neuroscience-based learning not only develops intellectual intelligence but also nurtures strong, empathetic, and humanistic character from an early age.